Endoscope-Based Digital Image Colorimetry for Nitrite Quantification in Processed Meats - Halim, Giovania; Wangsawijaya, Valerie; Gondowardojo, Grace Renata; Tjahjono, Martin (Universitas Jenderal Soedirman, 2026)
ABSTRACT. This study introduces a novel digital image colorimetry (DIC) approach for quantifying nitrites in processed meats, specifically sausages, to meet the demand for more accessible and cost-effective testing methods in food safety. By utilizing a custom-designed, 3D-printed imaging box to ensure standardized experimental conditions and incorporating an endoscope as the image sensor to reduce variations caused by smartphone camera specifications, the DIC method enhances the accuracy and reliability of analysis. The method achieved comparable accuracy to the Griess spectroscopy method (average error <5%) while providing significant advantages in portability, affordability, and accessibility for on-site nitrite concentration monitoring. Validation against the Griess spectroscopic technique demonstrated consistent results in quantifying nitrites in both commercial sausages and standard samples. This study highlights the utility of the DIC method as a viable tool for routine nitrite testing in the food industry, supporting consumer safety and regulatory compliance. Furthermore, the proposed approach paves the way for broader applications in food safety and analytical chemistry. Keywords: 3D-printed device, digital image colorimetry, endoscope sensor, food safety monitoring, Griess analysis, nitrite quantification